Human Resource Management and Skill Development in the Service Sector within the Framework of the SDGs: A Study on Distribution Companies in Denmark and Germany - Yusriani, Sri; Rekarti, Endi; Patiro, Shine Pintor Siolemba; Aftabi, Davoud (Dinasti International Journal of Digital Business Management, 2024)
This study aims to analyze the influence of human resource management on the development of work competencies among administrative staff in distribution companies in Denmark and Germany. The research focuses on how effective talent management contributes to the achievement of Sustainable Development Goal 8, which promotes decent work and economic growth. A quantitative research method was applied, using a non-experimental, cross-sectional design. The sample consisted of 86 employees, and data were collected through surveys and analyzed using SPSS v.25 software. The results showed a significant impact of human resource management on the improvement of work competencies, as indicated by the statistical model. The study concludes that proper human resource management can enhance employee skills and performance, contributing to organizational growth and sustainability.